The Effect of Mechanical Properties of the Capsular-Connected Complex Acetabulum Pedis on Movements in the Two-Segment Foot Model in Normal Foot and Flatfoot - Liabakh, A.P.; Lazariev, I.A.; Turchyn, O.A.; Piatkovskyi, V.M. (TERRA ORTHOPAEDICA, 2023)
Summary. The flatfoot remains a poorly defined clinical entity. Objective: to study the movements that occur in the foot under a single-support load on a two-segment model of the normal foot and flatfoot under different mechanical properties of the capsular-ligamentous complex acetabulum pedis. Materials and Methods. A two-segment model of the foot was developed, which consisted of anatomical hindfoot and forefoot. The connection between them was represented by a complex consisting of lig. calcaneonaviculare and the tendon of m. tibialis posterior. A decrease in the mechanical strength of the complex was represented by three types of tendon tissue degeneration according to Z.S. Rosenberg et al.: 0% – the norm, 25% – type І, 50% – type ІІ, and 75% – type ІІІ. The 3D finite element model was created using real foot skeletons from 12 patients with acquired flatfoot, obtained from 3D reconstructions with CT. The model was loaded with a force of 750 N from the plateau of the tibia in the direction of the ground surface. The adequacy of the model was assessed by examining the dependence of the simulation results with the values of the talo-navicular uncovered angle of the same patients. Results. The mutual movement of the segments forming the foot model progressively increased with a decrease in the strength of the capsular-ligamentous complex from 4.18 mm in the norm to 8.36 mm in type III degenerative changes. The linear nature of the dependence of total displacements on the decrease in the mechanical strength of the capsular-ligamentous complex is confirmed by the assessment of the adequacy of the model. Conclusions. The decrease in the mechanical strength of the capsular-ligamentous complex acetabulum pedis under a single-bearing load causes the mutual movement of segments of the model twice as large compared to the norm; the calculated dependence of movement/decrease in strength is linear.